PENGARUH GAYA KEPEMIMPINAN, BUDAYA ORGANISASI DAN MOTIVASI KERJA TERHADAP PRESTASI KERJA PEGAWAI DI LEMBAGA PEMASYARAKATAN KELAS IIB TEGAL - Fajar Setiawan; Tri Jaka Kartana (Multiplier: Jurnal Magister Manajemen, 2016)
The study is done to test the influence of style leadership, culture organiasasi and motivation work to work performance employees in an institution pemasyarakatan (lapas) a class IIB tegal. Population in research are always 50 people employees lapas kelas iib tegal. Research sample areas in a slovin, then set the sample as many as 44 were employees lapas class IIB tegal. The approach that was used in pene; litian this is the quantitative approach, data is collected through chief the questionnaire research that have been filled by respondents.A method of data analysis used is the method linear regression multiple, with data processing using sofware spss 20.0. The result of this research with this f simultaneous shows that style leadership, culture organization and motivation work together have had a positive impact and significantly to work performance employees. While with this t partial shows that style leadership, culture organization and motivation work haphazardly (partial) have had a positive impact and significantly to work performance employees. Keywords: a style of leadership, cultural organization, motivation work, work performance